Igor’ Alekseevič Pil’ščikov, Il retaggio scientifico del formalismo russo e le scienze umane moderne (ENTHYMEMA, 2011)
The criticism has recognized long ago the strong bond between the narratological theories of the 1960s and 1970s and the pioneering studies of the Formal school, and specifically of the Society for the Study of Poetic Language (Obščestvo po izučeniju poètičeskogo jazyka – OPOJAZ). This article, offering a brief reconstruction of the context of Russian Formalism, aims to dwell upon the methodological contributions provided by the scholars belonging to the Moscow Linguistic Circle (Moskovskij lingvističeskij kružok – MLK). Our purpose in this recollection is to shed a light on the influence that these approaches had on the modern humanities. More specifically, we will focus on the personality of Boris I. Jarcho and on the application of the method of inductive statistics on the study of the literary and linguistic object.